Ozone export from East Asia: The role of PAN. Issue 11 (7th June 2016) - Jiang, Zhe; Worden, John R.; Payne, Vivienne H.; Zhu, Liye; Fischer, Emily; Walker, Thomas; Jones, Dylan B. A.
Abstract: Peroxyacetyl nitrate (PAN) is an important ozone (O3 ) precursor. The lifetime of PAN is approximately 1 month in the free troposphere, and this allows O3 production to occur in pollution plumes at intercontinental distances from its source. In this study we use the Goddard Earth Observing System (GEOS)‐Chem global chemical transport model, new satellite measurements of PAN from the Aura Tropospheric Emission Spectrometer (TES), and data from the Arctic Research of the Composition of the Troposphere from Aircraft and Satellites (ARCTAS) field campaign over North America, to study the role of natural and anthropogenic Asian emissions on free tropospheric (900–400 hPa) PAN distributions and subsequent O3 production. Using the ARCTAS data with GEOS‐Chem, we show that while GEOS‐Chem is unbiased with respect to the aircraft data, TES version 7 PAN data are biased high for regions with surface temperatures colder than 285 K. However, GEOS‐Chem and TES measurements provide a consistent representation (within 15% difference) of PAN abundance over East Asia. Because of the good agreement between model and observations, we use the GEOS‐Chem model to evaluate the sources of PAN precursors and the effect of free tropospheric PAN on the export of O3 from Asia to North America. The GEOS‐Chem model results show that the largest contributors to free tropospheric PAN over Asia and the northern Pacific are anthropogenic and soil NOx emissions. Biomass burning emissions have important contributions to free tropospheric PAN over northern Pacific (25% in April), while the contribution from lightning over northern Pacific is significant in July (40%). Strong springtime transport in April results in more export of free tropospheric PAN and O3 from East Asian emissions. This free tropospheric PAN contributes about 35% to the abundance of free tropospheric O3 over western North America in spring and 25% in summer. Key Points: Agreement between model and TES PAN measurements Anthropogenic and soil NOx are the major sources of Asian free tropospheric PAN Important contribution (about 30%) of PAN on transpacific O3 transport